Perceived learning strategies of Malaysian university students in Web 2.0-based English as a second language informal learning - Che Wan Ida Rahimah Che Wan Ibrahim; Prain, Vaughan; Collet, Penelope (Penerbit UKM, 2014)
Web 2.0 popular platforms such as Facebook, YouTube and Wikis offer an emerging social networking practice, collective intelligence and a natural context to promote learner independence in informal ESL acquisition. This paper presents a review of recent research that investigates “the perceived learning strategies of Malaysian university students in Web 2.0-based informal learning of ESL”. The main research question considers how ESL learners account for the strategies of Web 2.0-based ESL learning when they engage with these tools in informal, learning settings. Questionnaires were used to generate quantitative data from the university student population (N=400) through an on-line self-reported survey. Results suggest that the majority of the Malaysian university students (ESL learners) surveyed use learning strategies with Web 2.0 tools for their English informal learning that are intentional and purposeful, and provide valuable lifelong learning experiences too. Powerful shared intentions and thoughts guide actions, shared practice and sociocultural mediation through Web 2.0 tools and roles in this informal learning activity system, locally and globally. These learners also seek help from their peers and their own independent research, using web 2.0 tools to practice in communicative language learning environments outside of the classroom in more relaxed atmosphere. This media has enabled students to adopt new learning behaviours, cooperative practice, mutual engagement and responsibilities consistent with the realities of a rapidly changing virtual community. The participants also expressed strong positive experiences and perceptions towards learning strategies with Web 2.0 tools towards their meaningful English informal learning.